Pattern recognition and classification : an introduction - Dougherty, Geoff (Springer, 2012)
This volume, both comprehensive and accessible, introduces all the key concepts in pattern recognition, and includes many examples and exercises that make it an ideal guide to an important methodology widely deployed in today's ubiquitous automated systems.